Discourse-directed framing as communication strategy alters students' concept of antibiotics and antibiotic resistance formation. Issue 4 (1st October 2020) - Beranek-Knauer, Heide; Walter, Hildrun; Paleczek, Dominik; Eder, Lucas; Jungwirth, Kerstin; Jungwirth, Helmut
ABSTRACT: One of the most urgent matters in current medicine is the preservation of antibiotic treatment options due to an increasing threat of antibiotic resistance in pathogenic microorganisms. Therefore, increasing awareness by adapted science education and communication regarding this topic is of the utmost importance. This article shows that an out-of-school laboratory course using active learning techniques is a valuable contribution to traditional teaching inciting personal and social responsibility. Attitude toward science (BRAINS), value of science to society (MATS), situational interest and emotions were tested. The participants' conception of antibiotics was evaluated by analysing follow-up mind maps. Generally, the laboratory course created positive feelings and situational interest. Compared to an instructor-directed frame, communication within an individually adapting discourse-directed frame conveyed more wide-spread perception of the topic, including societal and personal implications. The outcome of the study provides evidence that an out-of-school laboratory course can be a valuable tool for interest development in socio-scientific issues. Discourse-directed framing, in this environment, improves the individual ability to alter social and personal responsibility regarding science topics.